2015
DOI: 10.1126/science.aab0556
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive synergy between catechol and lysine promotes wet adhesion by surface salt displacement

Abstract: authors contributed equally to this work.One Sentence Summary: Siderophore-inspired, mussel foot protein mimetic adhesives resist oxidation and reveal a synergistic catechol-lysine interplay that enables wet adhesion to mineral surfaces Abstract: In physiological fluids and seawater, adhesion of synthetic polymers to solid surfaces is severely limited by high salt, pH, and hydration, yet these conditions have not deterred the evolution of effective adhesion by mussels. Mussel foot proteins provide insights abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
598
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 609 publications
(620 citation statements)
references
References 30 publications
15
598
0
7
Order By: Relevance
“…As shown by Butler et al 9. and Hwang et al.,11 mica‐adhesive molecules should likely contain both catechol and amino groups.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…As shown by Butler et al 9. and Hwang et al.,11 mica‐adhesive molecules should likely contain both catechol and amino groups.…”
mentioning
confidence: 75%
“…Butler et al. recently showed that a pending amine functionality is central to binding 9. To demonstrate this, a symmetric trichrysobactin was synthesized that bears three 2,3‐dihydroxybenzoyl moieties and a lysine tail.…”
mentioning
confidence: 99%
“…[49,50]. Several catechol-containing adhesive materials have been compared to their phenol-containing analogs and the switch from the bidentate interaction of catechol to the monodentate interaction of phenol results in a significant decrease in measured adhesion forces [46,51]. According to Bell theory ( = !…”
Section: Iron Coordination By Biological Catechols Catechol Siderophoresmentioning
confidence: 99%
“…The self-assembly of these materials is driven by entropy, where the initial electrostatic attraction between oppositely-charged macro-ions results in the release of small, bound counter-ions and the restructuring of water molecules [1][2][3][4]. Complex coacervates have a long history of use in the food [5][6][7][8][9][10][11][12][13] and personal care [14,15] industries, and have found increasing utility as a platform for drug and gene delivery [1][2][3][4], as well as underwater adhesives [5][6][7][8][9][10][11][12][13][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Coacervation has also recently been implicated in the formation of various biological assemblies [1,[14][15][16]55,…”
Section: Introductionmentioning
confidence: 99%